2021
DOI: 10.1007/s11738-021-03308-z
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols leaching and seed dormancy in carob (Ceratonia siliqua L.) in relation to hot water treatment

Abstract: Carob (Ceratonia siliqua L.) is a relevant element of the Mediterranean spontaneous vegetation. Moreover, it is useful in reforestation, and it is currently re-valued for sustainable agriculture in dryland areas. However, the difficulties tied to carob propagation (mainly seed dormancy) hamper its large-scale cultivation. In this paper, the effects of four seed treatments (no treatment [control], soaking at 70 °C and 90 °C in water, or in 96% sulphuric acid) on five carob genotypes germination were studied. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Several studies report different pretreatments effective in removing hard seeds in legumes. Sulfuric acid scarification is reported to be the best treatment in overcoming hard seeds and improving germination in carob ( Ceratonia siliqua L.) (Cavallaro et al., 2021), Vigna spp. (Wang et al., 2007), and Onobrychis species (Majidi & Barati, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies report different pretreatments effective in removing hard seeds in legumes. Sulfuric acid scarification is reported to be the best treatment in overcoming hard seeds and improving germination in carob ( Ceratonia siliqua L.) (Cavallaro et al., 2021), Vigna spp. (Wang et al., 2007), and Onobrychis species (Majidi & Barati, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The seed coat of Fabaceae constitutes of a single palisade layer of packed and elongated sclereids and nonuniformly thickened cell wall. Cuticle or waxy deposition, lignin, tannin, lipids, phenolics, callose, suberin, pigmentation etc are associated with hardseededness in legumes (Cavallaro et al, 2021;Lamichaney et al, 2017;Smykal et al, 2014). Remanandan et al (1991) reported the hardseededness to vary from 0% to 71% in pigeon pea.…”
Section: • Occurrence Of Dormancy In Wild Cajanus Andmentioning
confidence: 99%
See 2 more Smart Citations
“…of forty-four accessions used in the experiment. [1] C. scarabaeoides,[2] C. crassus,[3] C. cajanifolius,[4] R. minima,[5] R. bracteata, [6] R. rothii,[7] R. rufescens, [8] R. aurea,[9] C. lineatus,[10] C. platycarpus…”
mentioning
confidence: 99%